Application of the Quizizz Assisted Discovery Learning Model to Improve Mathematics Learning Outcomes of Grade III Students of SD Negeri 001 Bonai Darussalam - Aisyah, Aisyah; Elvina, Elvina (Journal of English Language and Education, 2026)
Mathematics learning in elementary schools has an important role in building understanding of concepts, but classroom practice still tends to be teacher-centered, so student learning outcomes are low. This research aims to improve Mathematics learning outcomes through the application of the Quizizz-assisted Discovery Learning model in grade III students of SD Negeri 001 Bonai Darussalam. The research used the Kemmis and McTaggart model of Classroom Action Research which was carried out in two cycles involving 23 students. Data was collected through learning outcome tests and observation of learning activities, then analyzed in a quantitative descriptive manner. The results showed an increase in the average score from 61 (35% completeness) in the pre-cycle to 76 (70%) in the first cycle and 93 (100%) in the second cycle. It was concluded that the integration of Discovery Learning and interactive digital evaluation was effective in improving students' understanding of concepts and learning engagement.